2020
DOI: 10.1016/j.matt.2020.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Instructive Polymers Control Macrophage Phenotype and Modulate the Foreign Body Response In Vivo

Abstract: Implantation of medical devices can result in inflammation. A large library of polymers is screened, and a selection found to promote macrophage differentiation towards pro-or anti-inflammatory phenotypes. The bioinstructive properties of these materials are validated within a rodent model. By identifying novel materials with immune-instructive properties, the relationship between material-immune cell interactions could be investigated, and this offers exciting possibilities to design novel bioinstructive mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 48 publications
1
76
0
Order By: Relevance
“…To minimize proinflammatory polarization of immune cells, implantable biomaterials are now being designed to promote anti-inflammatory polarizations. To this end, a high-throughput method for non-specific protein adsorption alongside macrophage adhesion and polarization, a component of inflammation (Brown et al, 2012), was developed using microprinted polymer spot arrays (Rostam et al, 2020). Polymer spot microarrays were assayed for cell attachment and macrophage polarization by microscopy and calprotectin/mannose receptor staining.…”
Section: High-throughput Methods To Measure Macrophage Adhesion and Amentioning
confidence: 99%
“…To minimize proinflammatory polarization of immune cells, implantable biomaterials are now being designed to promote anti-inflammatory polarizations. To this end, a high-throughput method for non-specific protein adsorption alongside macrophage adhesion and polarization, a component of inflammation (Brown et al, 2012), was developed using microprinted polymer spot arrays (Rostam et al, 2020). Polymer spot microarrays were assayed for cell attachment and macrophage polarization by microscopy and calprotectin/mannose receptor staining.…”
Section: High-throughput Methods To Measure Macrophage Adhesion and Amentioning
confidence: 99%
“…[ 279 ] Thus, specific chemical structure may have a profound effect on the regulation of the FBR, and other studies have also shown that different chemical modification will affect the polarization of macrophage phenotypes. [ 280,281 ] However, not all alginate microspheres with triazole structure have anti‐inflammatory property, which inferred that other chemical groups in these alginate derivatives will also affect inflammatory response and the FBR. The relationship between triazole groups and inflammatory response needs more in‐depth study.…”
Section: New Materials To Resist the Fbrmentioning
confidence: 99%
“…While the coronavirus is being combated with unified forces, a slower, silent revolution is taking place that will affect the health of even more people; the article by Rostam and co-workers in this issue of Matter is a feat of that. 1 Smart medical implants play an increasingly important role in human health care, and many unmet clinical challenges can be solved using biomaterials. But the proper interaction of the inorganic material surface with the biological system is of utmost importance for the success of the implant.…”
Section: Main Textmentioning
confidence: 99%
“… 8 A huge challenge specific for biomaterial engineering is that we need to bridge the complexity of both biology and materials science and want to have predictive models of it that hold not only at the cell but also at the tissue and organism level. For such a challenge, you need a well-stocked expedition and the expedition headed by Rostam and co-workers, 1 described in this issue of Matter was impressive. It was able to take all steps from material engineering, macrophage screening, data modeling, and testing the materials in an animal model.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation